1996
DOI: 10.1090/s0002-9939-96-03527-7
|View full text |Cite
|
Sign up to set email alerts
|

Weak separation properties for self-similar sets

Abstract: Abstract. We develop a theory for self-similar sets in R s that fulfil the weak separation property of Lau and Ngai, which is weaker than the open set condition of Hutchinson.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
66
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(66 citation statements)
references
References 9 publications
0
66
0
Order By: Relevance
“…In the self‐similar case, Zerner introduced the identity limit criterion, {φmonospacei1φmonospacej}i,jdoesnotaccumulatetotheidentity,and showed that it is equivalent to the weak separation condition. The self‐conformal case is more complicated since we cannot use inverses.…”
Section: Introductionmentioning
confidence: 99%
“…In the self‐similar case, Zerner introduced the identity limit criterion, {φmonospacei1φmonospacej}i,jdoesnotaccumulatetotheidentity,and showed that it is equivalent to the weak separation condition. The self‐conformal case is more complicated since we cannot use inverses.…”
Section: Introductionmentioning
confidence: 99%
“…Then #scriptVk=bolde1Bk1t and trueprefixlimk(bolde1Bk1t)1/k=ρ. Therefore, by [, Theorem 2], we have prefixdimHK=trueprefixlimklog#scriptVkklogr=logρlogr.…”
Section: Lipschitz Equivalence Of Self‐similar Setsmentioning
confidence: 93%
“…In the absence of the OSC, it is much harder to compute the Hausdorff dimension. Nevertheless, the dimension formula is still attainable for a large class of self‐similar sets with overlaps (see ). Under our setting, we prefer to use the following formula.…”
Section: Lipschitz Equivalence Of Self‐similar Setsmentioning
confidence: 99%
“…We remark that the above definition for the WSC is equivalent to that given by Lau and Ngai in [21], provided that K is not contained in a hyperplane of R d . For a proof, see Zerner [41,Theorem 1]. It is known that the open set condition implies the WSC [21].…”
Section: Preliminaries and The Wscmentioning
confidence: 99%